On The Ngbugu Vowel System - Olson, Kenneth (My University, 2022)
Previous researchers have posited asymmetric oral vowel systems for Ngbugu and other Banda languages. The present analysis shows that Ngbugu has a symmetric ten-vowel system which includes one interior vowel /ə/ and lacks vowel harmony. It also supports and refines Boyeldieu & Cloarec-Heiss’s (2001) proposed Proto-Banda vowel system. The affinities of the resulting proto vowel system to those of nearby languages could facilitate the comparison of vowel systems across the region in order to test hypotheses about shared inheritance or borrowing. Possible explanations for the lack of vowel harmony are suggested.
Keywords: Ngbugu; vowel system; Banda language